Penerapan Audit SDM Untuk Melihat Pengaruh Program Pelatihan Dalam Meningkatkan Produktivitas Kerja Karyawan PT. Sumber Jaya Fastindo - Herny Ria Mandag; Hwihanus Hwihanus (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Human Resources (HR) Audit is an effort to improve the quality of human resources in a company. One of the objectives of an HR audit is to see the effect of training programs in increasing employee work productivity. This training aims to analyze the effect of the training program on the work productivity of PT employees. Sumber Jaya Fastindo. This research uses a survey method for employees of PT. Sumber Jaya Fastindo. Data was collected through questionnaires. The research results show that the training program has a positive and significant influence on the work productivity of PT employees. Sumber Jaya Fastindo. This means that training programs can increase employee work productivity. Therefore, companies need to pay attention to the quality of the training programs provided to employees. Training programs must be well designed and tailored to employee needs. Apart from that, companies also need to evaluate the training programs that have been implemented to see their effectiveness.